Method for improving mechanical properties of carbon-carbon composites by iron ion doping modification
Through iron ion doping modification treatment of graphite and carbon fibers, functional slurries and modified carbon fibers are formed, which solves the problem of insufficient compressive resistance and high-temperature ultraviolet performance of carbon-carbon composite materials, and achieves high strength and stability mechanical properties, especially Excellent performance under high temperature and ultraviolet radiation.
Patent Information
- Application Number
- CN202411281022.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-13
AI Technical Summary
The existing carbon-carbon composite materials have a lot of mechanical properties in compressive resistance and high temperature environments, and have poor UV radiation resistance, mainly due to poor compatibility between graphite and matrix materials and poor bonding between carbon fiber and slurry.
Through iron ion doping modification treatment of graphite and carbon fiber, functional slurries and modified carbon fibers are prepared, and ball milling, spraying, ultrasonic treatment and aminoation are carried out in specific process flows to form a stable network structure and a good interface Combination improves the homogeneity and bonding properties of the material.
It significantly improves the compressive strength and high temperature resistance of carbon-carbon composite materials, ensures the stability of mechanical properties under high temperature and ultraviolet radiation, with a density of 1.35-1.38g/cm3, a compressive strength of 189-195MPa, and a flexural strength. It is 170-176MPa and the bending strength is 238-246MPa.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of carbon-carbon composite materials, and particularly relates to a method for improving the mechanical properties of a carbon-carbon composite material by iron ion doping and modification. Background Art
[0002] Carbon-carbon composites are carbon-matrix composites reinforced with carbon fibers and their fabrics. They are widely used in the aerospace industry due to their good high temperature resistance, good shock resistance and mechanical properties, and small thermal expansion coefficient. Carbon-carbon composites also have high friction stability and a small friction coefficient, and are widely used in brake discs of high-speed trains and airplanes, with good development prospects.
[0003] In the preparation method of carbon-carbon composite materials, a fiber winding machine is usually used to pass carbon fibers through a slurry at a uniform speed. After winding to a certain size, the carbon fibers are cut, dried, stacked, and placed in a graphite mold for hot pressing and sintering to obtain a product. The slurry usually uses graphite as an aggregate and asphalt and / or resin as a matrix material. The graphite in the slurry has poor compatibility with the matrix material and weak bonding, resulting in poor dispersion and homogeneity of the slurry. In addition, it is not easy for the carbon fibers to form a good interface with the matrix material in the slurry, thereby affecting the mechanical properties of the carbon-carbon composite material.
[0004] CN117534499A discloses a method for preparing a carbon-carbon composite material, specifically disclosing that carbon fiber cloth is pre-impregnated with a resin mixture, and then subjected to a curing treatment to obtain a carbon fiber prepreg, and then the carbon fiber prepreg is laminated to form a multilayer structure, and then pressed, and subjected to a carbonization treatment and a graphitization treatment to obtain a carbon-carbon composite material; the resin mixture comprises a phenolic resin, a filler, a coupling agent, a accelerator, and an organic solvent;
[0005] The preparation method improves the compatibility between the resin and the carbon fiber matrix, so that the resin can better bond with the carbon fiber, improves the bonding force between the resin and the matrix, and enhances the strength and heat resistance of the carbon-carbon composite material;
[0006] However, the carbon-carbon composite material produced by this patent has poor compressive properties, suffers from a large loss of mechanical properties under high temperature conditions, and has poor resistance to ultraviolet radiation. Summary of the invention
[0007] In order to solve the technical problems existing in the prior art, the present invention provides a method for improving the mechanical properties of carbon-carbon composite materials by iron ion doping modification, which has high compressive strength, excellent high temperature resistance and ultraviolet radiation resistance.
[0008] In view of the above technical problems, the present invention adopts the following technical solutions:
[0009] The method for improving the mechanical properties of carbon-carbon composite materials by iron ion doping modification includes preparing functional slurry, modifying carbon fiber, preparing carbon fiber preform, compounding and post-processing steps, and the specific operations are as follows:
[0010] 1. Preparation of functional slurry
[0011] (1) Preprocessing
[0012] The graphite is placed in deionized water for ball milling, with zirconia balls with a diameter of 5 mm as grinding balls, a ball-to-material ratio of 3-5:1, and a ball milling time of 37-43 minutes. After the ball milling is completed, the graphite is dried at 112-118° C. to obtain pretreated graphite;
[0013] The particle size of the graphite is 210-230nm;
[0014] The mass ratio of graphite to deionized water is 9.5-10.4:60-67;
[0015] (2) Modification
[0016] The pretreated graphite is placed in a closed container, and then the modifier is sprayed at a spray rate of 2.8-3.2 g / min. The mixture is stirred while spraying at a stirring rate of 265-275 rpm. After the spraying is completed, the pressure is increased to 1.6-1.8 MPa, the temperature is controlled to 60-64° C., the rotation speed is increased to 343-356 rpm, and the stirring is continued for 2.4-2.6 hours. After the stirring is completed, the mixture is filtered, washed, and dried to obtain the modified graphite.
[0017] The mass ratio of the pretreated graphite to the modifier is 8.7-9.1:55-60;
[0018] The modifier is composed of anhydrous ethanol, diisopropanolamine, castor oil and Tween 80, and the mass ratio of anhydrous ethanol, diisopropanolamine, castor oil and Tween 80 is 76-80:1.3-1.5:1.0-1.2:1.8-2.2;
[0019] (3) Functionalization
[0020] Add modified graphite and dimethyl sulfoxide to a reaction container, stir evenly, heat to 65-70°C at a rate of 1.4-1.6°C / min and stir, cool to 40-45°C at a rate of 0.8-1.2°C / min, add epoxidized soybean oil and tin tetrachloride, and perform ultrasonic treatment, wherein the ultrasonic time is 20-24min, the ultrasonic power is 120-130W, and the ultrasonic frequency is 23-30kHz. After the ultrasonic treatment, stir and react for 6.2-6.5h. After the reaction is completed, filter, wash, and dry to obtain functional graphite.
[0021] The mass volume ratio of the modified graphite, dimethyl sulfoxide, epoxy soybean oil and tin tetrachloride is 10.2-10.6 g: 270-290 mL: 0.40-0.45 g: 0.01-0.02 g;
[0022] (4) Mixing
[0023] The coal tar powder and the iron ion source are mixed and subjected to ultrasonic oscillation treatment for 24-30 minutes at a frequency of 42-47kHz. After the ultrasonic oscillation treatment, the mixture is put into a polytetrafluoroethylene spherical ink tank, and functional graphite is added for ball milling treatment. Zirconia balls with a diameter of 5 mm are used as grinding balls, and anhydrous ethanol is added as a solvent medium. The ball milling time is 7.8-8.2 hours, the ball milling speed is 172-185 rpm, and the ball-to-material ratio is 3-5:1. Then, methyl cellulose solution, polyethylene glycol 400 and Triton X-100 are added to continue the ball milling treatment. The ball milling time is 1.7-2.3 hours, the ball milling speed is 232-247 rpm, and the ball-to-material ratio is 4-6:1. After the ball milling is completed, a functional slurry is obtained;
[0024] The iron ion source is one of ferric chloride and ferric oxide;
[0025] The particle size of the coal tar powder is 95-110 mesh;
[0026] The mass fraction of the methyl cellulose solution is 3.6-4.0%;
[0027] The mass volume ratio of the coal tar powder, iron ion source, functional graphite, anhydrous ethanol, methyl cellulose solution, polyethylene glycol 400 and Triton X-100 is 96-99g:1.0-4.0g:13.4-14.0g:38-42g:58-62g:0.8-1.2mL:0.9-1.1mL.
[0028] 2. Modified carbon fiber
[0029] (1) Activation
[0030] The carbon fiber is placed in a radio frequency low-pressure plasma device for plasma treatment, the treatment atmosphere is oxygen, the treatment pressure is 6.7-7.2Pa, the treatment power is 74-80W, the oxygen flow rate is controlled to be 38-43sccm, the treatment time is 4.5-5.5min, and after the treatment, it is placed in an acid solution for soaking, the soaking time is 2.3-2.7h, and the soaking temperature is 81-85°C. After the soaking, it is washed and dried to obtain activated carbon fiber;
[0031] The length of the carbon fiber is 4.5-5.5 cm, and the carbon content is 97.0-98.0%;
[0032] The mass ratio of the carbon fiber to the acid solution is 6.3-6.7:38-42;
[0033] The acid solution is a mixture of a nitric acid solution and a sulfuric acid solution, the volume ratio of the nitric acid solution to the sulfuric acid solution is 0.7-1.2:1, the mass concentration of the nitric acid solution is 60-64%, and the mass concentration of the sulfuric acid solution is 56-60%;
[0034] (2) Amination
[0035] Put the activated carbon fiber into the toluene solution, stir evenly, add fatty acid polyethylene glycol ester and polyvinyl pyrrolidone, heat to 56-60°C at a rate of 0.8-1.2°C / min, stir at 310-330rpm for 23-30min, add N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane after stirring, heat to 90-94°C at a rate of 0.6-1.0°C / min, stir at 210-230rpm for 11-13h, filter, wash and dry after the reaction to obtain modified carbon fiber;
[0036] The mass concentration of the toluene solution is 63-68%;
[0037] The mass volume ratio of the activated carbon fiber, toluene solution, fatty acid polyethylene glycol ester, polyvinyl pyrrolidone, and N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane is 5.6-6.0 g: 280-320 mL: 0.6-0.8 g: 0.9-1.1 g: 0.62-0.66 g.
[0038] 3. Preparation of carbon fiber preform
[0039] The modified carbon fiber is combed and air-laid to obtain a carbon fiber web, wherein the weight of the carbon fiber web is 60-64 g / m 2 ; Prepare 12K carbon fiber filaments with a carbon content of 97.0-98.0% into continuous fiber carbon cloth, and control the gram weight of the continuous fiber carbon cloth to 370-385g / m 2 ; The carbon fiber preform is prepared by alternately stacking the carbon fiber web and the continuous fiber carbon cloth using needle punching technology;
[0040] The angle of alternating stacking is controlled to be 0°, and the alternating stacking ratio of carbon fiber mesh and continuous fiber carbon cloth is 1:1, that is, a layer of carbon fiber mesh and a layer of continuous fiber carbon cloth are alternately stacked; the needle punching density is 32-35 needles / cm 2 The needle penetration depth is 9-12 cm, and the density of the carbon fiber preform is 0.62-0.66 g / cm 3 .
[0041] 4. Compound
[0042] A carbon fiber preform and 3.5-4.5 times the weight of the functional slurry are added into an impregnation container for impregnation treatment. The impregnation time is 52-57 minutes and the impregnation pressure is 1.6-2.0 MPa. After the impregnation is completed, the preform is taken out and then placed at 115-125°C for heat preservation and curing for 2.8-3.2 hours. The temperature is increased to 148-152°C at a rate of 1.8-2.2°C / min, and the preform is heat-insulated and cured at 148-152°C for 3.7-4.3 hours. The temperature is increased to 175-185°C at a rate of 0.8-1.2°C / min, and the preform is heat-insulated and cured at 175-185°C for 4.7-5.3 hours. The temperature is increased to 197-204°C at a rate of 0.5-0.8°C / min, and the preform is heat-insulated and cured at 197-204°C for 5.8-6.2 hours. After the heat preservation and curing is completed, an impregnated body is obtained.
[0043] 5. Post-processing
[0044] The impregnated body is placed in a carbonization furnace and carbonized in an argon atmosphere. The heating rate is 4.7-5.3℃ / min, the carbonization temperature is 1480-1520℃, and the carbonization time is 1.4-1.6h. After the carbonization is completed, a carbonized body is obtained. Then the carbonized body is placed in an impregnation container and put into 3.5-4.5 times the mass of the functional slurry for impregnation treatment again. The impregnation time is 105-114min, the impregnation pressure is 2.0-2.4MPa, and the impregnation temperature is 175-183℃. After the impregnation is completed, it is placed in a carbonization furnace and carbonized in an argon atmosphere. The heating rate is 4.7-5.3℃ / min, the carbonization temperature is 1760-1820℃, and the carbonization time is 1.4-1.8h. After the carbonization is completed, a carbon-carbon composite material is obtained.
[0045] Compared with the prior art, the present invention has achieved the following beneficial effects:
[0046] 1. The present invention performs functional treatment on graphite, firstly performs modification treatment on graphite, which can not only enhance the dispersion performance of graphite, but also increase the reactive groups on the surface of graphite, and then after functional treatment, the surface active groups of modified graphite undergo ring-opening reaction with epoxy soybean oil under the catalytic action of tin tetrachloride to form a stable network structure, and the introduced epoxy soybean oil contains hydrophobic alkyl long chains, which further enhances the compatibility with asphalt, and in the slurry preparation step, the coal tar powder is mixed with the iron ion source, and combined with the auxiliary agent component, the homogeneity and bonding performance of the slurry are improved; the present invention performs modification on carbon fiber, firstly performs oxygen plasma treatment and acid leaching on it, which can increase the surface roughness of carbon fiber, thereby activating it, and then performs amination treatment, so that the surface of carbon fiber is grafted with amino groups, which can react with epoxy groups in the functional slurry, thereby improving the binding force between the carbon fiber preform and the functional slurry, forming a stable structure and a good bonding interface, and enhancing the mechanical properties and stability of the carbon-carbon composite material;
[0047] The present invention adopts a specific method to prepare functional slurry and modified carbon fiber. The functional slurry has good homogeneity, and the components are tightly and stably combined. In the impregnation step, the carbon fiber preform and the functional slurry have a good bonding interface, and the impregnation is sufficient and uniform, so that the carbon fiber preform and the functional slurry are fully and firmly combined, and the structure is stable, thereby ensuring the compressive strength of the carbon-carbon composite material, and the mechanical properties are excellent and stable. Under high temperature and ultraviolet radiation, it still has good mechanical properties;
[0048] 2. The carbon-carbon composite material prepared by the method of the present invention has a density of 1.35-1.38 g / cm 3 ;
[0049] 3. The carbon-carbon composite material prepared by the method of the present invention has a compressive strength of 189-195 MPa, a flexural strength of 170-176 MPa, and a bending strength of 238-246 MPa;
[0050] 4. The carbon-carbon composite material prepared by the method of the present invention is first heated to 800°C at a rate of 10°C / min, placed at 800°C for 48 hours, cooled naturally to room temperature, and then placed at a strength of 500W / cm 2 The samples were irradiated under ultraviolet light for 72 hours, then heated to 1400°C at a rate of 5°C / min, allowed to stand at 1400°C for 24 hours, and naturally cooled to room temperature. The compressive strength was measured again to be 180-188MPa, the flexural strength was 159-167MPa, and the bending strength was 225-235MPa. DETAILED DESCRIPTION
[0051] In order to more clearly understand the technical features, purposes and effects of the present invention, specific embodiments of the present invention are now described.
[0052] Example 1
[0053] 1. Preparation of functional slurry
[0054] (1) Preprocessing
[0055] 10 g of graphite was placed in 63 g of deionized water for ball milling, with zirconia balls with a diameter of 5 mm as grinding balls, a ball-to-material ratio of 4:1, and a ball milling time of 40 min. After the ball milling, the graphite was dried at 115° C. to obtain pretreated graphite.
[0056] The particle size of the graphite is 220 nm;
[0057] (2) Modification
[0058] 8.9 g of pretreated graphite was placed in a closed container, and then 57 g of modifier was sprayed at a spray rate of 3.0 g / min. Stirring was performed while spraying at a stirring rate of 270 rpm. After the spraying was completed, the pressure was increased to 1.7 MPa, the temperature was controlled to 62° C., the speed was increased to 350 rpm, and stirring was continued for 2.5 h. After the stirring was completed, the modified graphite was filtered, washed, and dried to obtain the modified graphite.
[0059] The modifier is composed of anhydrous ethanol, diisopropanolamine, castor oil and Tween 80, and the mass ratio of anhydrous ethanol, diisopropanolamine, castor oil and Tween 80 is 78:1.4:1.1:2.0;
[0060] (3) Functionalization
[0061] Add 10.4 g of modified graphite and 280 mL of dimethyl sulfoxide into the reaction container, stir evenly, heat to 67 ° C at a rate of 1.5 ° C / min and stir, stir evenly, cool to 42 ° C at a rate of 1.0 ° C / min, add 0.43 g of epoxy soybean oil and 0.01 g of tin tetrachloride, and carry out ultrasonic treatment. The ultrasonic time is 22 min, the ultrasonic power is 126 W, and the ultrasonic frequency is 27 kHz. After the ultrasonic treatment, stir the reaction for 6.3 h. After the reaction, filter, wash and dry to obtain functional graphite.
[0062] (4) Mixing
[0063] 96g coal tar powder and 4.0g ferric chloride were mixed and subjected to ultrasonic oscillation treatment for 27min at a frequency of 45kHz. After the ultrasonic oscillation treatment, the mixture was put into a polytetrafluoroethylene ball ink tank, 13.7g functional graphite was added for ball milling treatment, zirconia balls with a diameter of 5mm were used as grinding balls, 40g anhydrous ethanol was added as a solvent medium, the ball milling time was 8.0h, the ball milling speed was 180rpm, and the ball-to-material ratio was 4:1, and then 60g methylcellulose solution, 1.0mL polyethylene glycol 400 and 1.0mL Triton X-100 were added to continue the ball milling treatment, the ball milling time was 2.0h, the ball milling speed was 240rpm, and the ball-to-material ratio was 5:1. After the ball milling was completed, a functional slurry was obtained;
[0064] The particle size of the coal tar powder is 100 mesh;
[0065] The mass fraction of the methyl cellulose solution is 3.8%.
[0066] 2. Modified carbon fiber
[0067] (1) Activation
[0068] 6.5g of carbon fiber was placed in a radio frequency low-pressure plasma device for plasma treatment, the treatment atmosphere was oxygen, the treatment pressure was 7Pa, the treatment power was 76W, the oxygen flow rate was controlled to be 40sccm, the treatment time was 5.0min, and after the treatment, it was placed in a 40g acid solution for immersion, the immersion time was 2.5h, and the immersion temperature was 83°C. After the immersion, it was washed and dried to obtain activated carbon fiber;
[0069] The length of the carbon fiber is 5 cm and the carbon content is 97.5%;
[0070] The acid solution is a mixture of a nitric acid solution and a sulfuric acid solution, the volume ratio of the nitric acid solution to the sulfuric acid solution is 1:1, the mass concentration of the nitric acid solution is 62%, and the mass concentration of the sulfuric acid solution is 58%;
[0071] (2) Amination
[0072] 5.8 g of activated carbon fiber was added to 300 mL of toluene solution, and after stirring evenly, 0.7 g of fatty acid polyethylene glycol ester and 1.0 g of polyvinyl pyrrolidone were added, and the temperature was raised to 58 ° C at a rate of 1.0 ° C / min, and stirred at 320 rpm for 26 min. After the stirring was completed, 0.64 g of N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane was added, and the temperature was raised to 92 ° C at a rate of 0.8 ° C / min, and the reaction was stirred at 220 rpm for 12 h. After the reaction was completed, it was filtered, washed and dried to obtain modified carbon fiber;
[0073] The mass concentration of the toluene solution is 65%.
[0074] 3. Preparation of carbon fiber preform
[0075] The modified carbon fiber is combed and air-laid to obtain a carbon fiber web. The weight of the carbon fiber web is 62 g / m 2 ; Prepare 12K carbon fiber filaments with a carbon content of 97.5% into continuous fiber carbon cloth, and control the gram weight of the continuous fiber carbon cloth to 380g / m 2 ; The carbon fiber preform is prepared by alternately stacking the carbon fiber web and the continuous fiber carbon cloth using needle punching technology;
[0076] The angle of alternating stacking is controlled to be 0°, and the alternating stacking ratio of carbon fiber mesh and continuous fiber carbon cloth is 1:1, that is, a layer of carbon fiber mesh and a layer of continuous fiber carbon cloth are alternately stacked; the needle punching density is 34 needles / cm 2 The needle penetration depth is 10 cm and the density of the carbon fiber preform is 0.64 g / cm 3 .
[0077] 4. Compound
[0078] A carbon fiber preform and 4.0 times the mass of the functional slurry are added to the impregnation container for impregnation treatment. The impregnation time is 55 minutes and the impregnation pressure is 1.8 MPa. After the impregnation, it is taken out and then placed at 120°C for heat preservation and curing for 3.0 hours, the temperature is increased to 150°C at a rate of 2°C / min, and the temperature is kept at 150°C for 4.0 hours. The temperature is increased to 180°C at a rate of 1.0°C / min, and the temperature is kept at 180°C for 5.0 hours. The temperature is increased to 200°C at a rate of 0.6°C / min, and the temperature is kept at 200°C for 6.0 hours. After the heat preservation and curing is completed, an impregnated body is obtained.
[0079] 5. Post-processing
[0080] The impregnated body is placed in a carbonization furnace and carbonized in an argon atmosphere. The heating rate is 5°C / min, the carbonization temperature is 1500°C, and the carbonization time is 1.5h. After the carbonization is completed, a carbonized body is obtained. Then the carbonized body is placed in an impregnation container and put into 4 times the mass of functional slurry for impregnation again. The impregnation time is 110min, the impregnation pressure is 2.2MPa, and the impregnation temperature is 180°C. After the impregnation is completed, it is placed in a carbonization furnace and carbonized in an argon atmosphere. The heating rate is 5°C / min, the carbonization temperature is 1800°C, and the carbonization time is 1.5h. After the carbonization is completed, a carbon-carbon composite material is obtained.
[0081] Example 2
[0082] 1. Preparation of functional slurry
[0083] (1) Preprocessing
[0084] 9.5 g of graphite was placed in 60 g of deionized water for ball milling, with zirconia balls with a diameter of 5 mm as grinding balls, a ball-to-material ratio of 3:1, and a ball milling time of 37 min. After the ball milling, the graphite was dried at 112 ° C to obtain pretreated graphite.
[0085] The particle size of the graphite is 210 nm;
[0086] (2) Modification
[0087] 8.7 g of pretreated graphite was placed in a closed container, and then 55 g of modifier was sprayed at a spray rate of 2.8 g / min. Stirring was performed while spraying at a stirring rate of 265 rpm. After the spraying was completed, the pressure was increased to 1.6 MPa, the temperature was controlled at 60° C., the speed was increased to 343 rpm, and stirring was continued for 2.4 h. After the stirring was completed, the modified graphite was filtered, washed, and dried to obtain the modified graphite.
[0088] The modifier is composed of anhydrous ethanol, diisopropanolamine, castor oil and Tween 80, and the mass ratio of anhydrous ethanol, diisopropanolamine, castor oil and Tween 80 is 76:1.3:1.0:1.8;
[0089] (3) Functionalization
[0090] Add 10.2g of modified graphite and 270mL of dimethyl sulfoxide into the reaction container, stir evenly, heat to 65°C at a rate of 1.4°C / min and stir, stir evenly, cool to 40°C at a rate of 0.8°C / min, add 0.40g of epoxy soybean oil and 0.01g of tin tetrachloride, and carry out ultrasonic treatment. The ultrasonic time is 20min, the ultrasonic power is 120W, and the ultrasonic frequency is 23kHz. After the ultrasonic treatment, stir the reaction for 6.2h. After the reaction, filter, wash and dry to obtain functional graphite.
[0091] (4) Mixing
[0092] 98g coal tar powder and 2.0g ferric chloride were mixed and subjected to ultrasonic oscillation treatment for 24min at a frequency of 42kHz. After the ultrasonic oscillation treatment, the mixture was put into a polytetrafluoroethylene ball ink tank, 13.4g functional graphite was added for ball milling treatment, zirconia balls with a diameter of 5mm were used as grinding balls, 38g anhydrous ethanol was added as a solvent medium, the ball milling time was 7.8h, the ball milling speed was 172rpm, and the ball-to-material ratio was 3:1, and then 58g methylcellulose solution, 0.8mL polyethylene glycol 400 and 0.9mL Triton X-100 were added to continue the ball milling treatment, the ball milling time was 1.7h, the ball milling speed was 232rpm, and the ball-to-material ratio was 4:1. After the ball milling was completed, a functional slurry was obtained;
[0093] The particle size of the coal tar powder is 95 mesh;
[0094] The mass fraction of the methyl cellulose solution is 3.6%.
[0095] 2. Modified carbon fiber
[0096] (1) Activation
[0097] 6.3g of carbon fiber was placed in a radio frequency low-pressure plasma device for plasma treatment, the treatment atmosphere was oxygen, the treatment pressure was 6.7Pa, the treatment power was 74W, the oxygen flow rate was controlled to be 38sccm, the treatment time was 4.5min, after the treatment, it was placed in a 38g acid solution for immersion, the immersion time was 2.3h, the immersion temperature was 81°C, after the immersion, it was washed and dried to obtain activated carbon fiber;
[0098] The length of the carbon fiber is 4.5 cm and the carbon content is 97.0%;
[0099] The acid solution is a mixture of a nitric acid solution and a sulfuric acid solution, the volume ratio of the nitric acid solution to the sulfuric acid solution is 1.2:1, the mass concentration of the nitric acid solution is 60%, and the mass concentration of the sulfuric acid solution is 56%;
[0100] (2) Amination
[0101] 5.6 g of activated carbon fiber was added to 280 mL of toluene solution, and after stirring evenly, 0.6 g of fatty acid polyethylene glycol ester and 0.9 g of polyvinyl pyrrolidone were added, and the temperature was raised to 56 ° C at a rate of 0.8 ° C / min, and stirred at 310 rpm for 23 min. After the stirring was completed, 0.62 g of N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane was added, and the temperature was raised to 90 ° C at a rate of 0.6 ° C / min, and the reaction was stirred at 210 rpm for 11 hours. After the reaction was completed, it was filtered, washed and dried to obtain modified carbon fiber;
[0102] The mass concentration of the toluene solution is 63%.
[0103] 3. Preparation of carbon fiber preform
[0104] The modified carbon fiber is combed and air-laid to obtain a carbon fiber web. The weight of the carbon fiber web is 60 g / m 2 ; Prepare 12K carbon fiber filaments with a carbon content of 97.0% into continuous fiber carbon cloth, and control the gram weight of the continuous fiber carbon cloth to 370g / m 2 ; The carbon fiber preform is prepared by alternately stacking the carbon fiber web and the continuous fiber carbon cloth using needle punching technology;
[0105] The angle of alternating stacking is controlled to be 0°, and the alternating stacking ratio of carbon fiber mesh and continuous fiber carbon cloth is 1:1, that is, a layer of carbon fiber mesh and a layer of continuous fiber carbon cloth are alternately stacked; the needle punching density is 32 needles / cm 2 The needle penetration depth is 9 cm and the density of the carbon fiber preform is 0.62 g / cm 3 .
[0106] 4. Compound
[0107] A carbon fiber preform and 3.5 times the mass of the functional slurry are added to the impregnation container for impregnation treatment. The impregnation time is 52 minutes and the impregnation pressure is 1.6 MPa. After the impregnation is completed, it is taken out and then placed at 115°C for heat preservation and curing for 2.8 hours, the temperature is increased to 148°C at a rate of 1.8°C / min, and the temperature is kept at 148°C for 3.7 hours. The temperature is increased to 175°C at a rate of 0.8°C / min, and the temperature is kept at 175°C for 4.7 hours. The temperature is increased to 197°C at a rate of 0.5°C / min, and the temperature is kept at 197°C for 5.8 hours. After the insulation and curing is completed, an impregnated body is obtained.
[0108] 5. Post-processing
[0109] The impregnated body is placed in a carbonization furnace and carbonized under an argon atmosphere. The heating rate is 4.7°C / min, the carbonization temperature is 1480°C, and the carbonization time is 1.4h. After the carbonization is completed, a carbonized body is obtained. Then the carbonized body is placed in an impregnation container and put into 3.5 times the mass of the functional slurry for impregnation again. The impregnation time is 105min, the impregnation pressure is 2.0MPa, and the impregnation temperature is 175°C. After the impregnation is completed, it is placed in a carbonization furnace and carbonized under an argon atmosphere. The heating rate is 4.7°C / min, the carbonization temperature is 1760°C, and the carbonization time is 1.8h. After the carbonization is completed, a carbon-carbon composite material is obtained.
[0110] Example 3
[0111] 1. Preparation of functional slurry
[0112] (1) Preprocessing
[0113] 10.4 g of graphite was placed in 67 g of deionized water for ball milling, with zirconia balls with a diameter of 5 mm as grinding balls, a ball-to-material ratio of 5:1, and a ball milling time of 43 min. After the ball milling, the graphite was dried at 118 ° C to obtain pretreated graphite.
[0114] The particle size of the graphite is 230 nm;
[0115] (2) Modification
[0116] 9.1 g of pretreated graphite was placed in a closed container, and then 60 g of modifier was sprayed at a spray rate of 3.2 g / min. Stirring was performed while spraying at a stirring rate of 275 rpm. After the spraying was completed, the pressure was increased to 1.8 MPa, the temperature was controlled to 64°C, the speed was increased to 356 rpm, and stirring was continued for 2.6 h. After the stirring was completed, the modified graphite was filtered, washed, and dried to obtain the modified graphite.
[0117] The modifier is composed of anhydrous ethanol, diisopropanolamine, castor oil and Tween 80, and the mass ratio of the anhydrous ethanol, diisopropanolamine, castor oil and Tween 80 is 80:1.5:1.2:2.2;
[0118] (3) Functionalization
[0119] Add 10.6g of modified graphite and 290mL of dimethyl sulfoxide into the reaction container, stir evenly, heat to 70°C at a rate of 1.6°C / min and stir, stir evenly, cool to 45°C at a rate of 1.2°C / min, add 0.45g of epoxy soybean oil and 0.02g of tin tetrachloride, and carry out ultrasonic treatment. The ultrasonic time is 24min, the ultrasonic power is 130W, and the ultrasonic frequency is 30kHz. After the ultrasonic treatment, stir the reaction for 6.5h. After the reaction, filter, wash and dry to obtain functional graphite.
[0120] (4) Mixing
[0121] 99g coal tar powder and 1.0g iron oxide were mixed and subjected to ultrasonic oscillation treatment for 30min at a frequency of 47kHz. After the ultrasonic oscillation treatment, the mixture was put into a polytetrafluoroethylene ball ink tank, and 14.0g functional graphite was added for ball milling treatment. Zirconia balls with a diameter of 5mm were used as grinding balls. 42g anhydrous ethanol was added as a solvent medium. The ball milling time was 8.2h, the ball milling speed was 185rpm, and the ball-to-material ratio was 5:1. Then, 62g methylcellulose solution, 1.2mL polyethylene glycol 400 and 1.1mL Triton X-100 were added to continue the ball milling treatment. The ball milling time was 2.3h, the ball milling speed was 247rpm, and the ball-to-material ratio was 6:1. After the ball milling was completed, a functional slurry was obtained.
[0122] The particle size of the coal tar powder is 110 mesh;
[0123] The mass fraction of the methyl cellulose solution is 4.0%.
[0124] 2. Modified carbon fiber
[0125] (1) Activation
[0126] 6.7g of carbon fiber was placed in a radio frequency low-pressure plasma device for plasma treatment, the treatment atmosphere was oxygen, the treatment pressure was 7.2Pa, the treatment power was 80W, the oxygen flow rate was controlled to be 43sccm, the treatment time was 5.5min, and after the treatment, it was placed in a 42g acid solution for immersion, the immersion time was 2.7h, and the immersion temperature was 85°C. After the immersion, it was washed and dried to obtain activated carbon fiber;
[0127] The length of the carbon fiber is 5.5 cm and the carbon content is 98.0%;
[0128] The acid solution is a mixture of a nitric acid solution and a sulfuric acid solution, the volume ratio of the nitric acid solution to the sulfuric acid solution is 0.7:1, the mass concentration of the nitric acid solution is 64%, and the mass concentration of the sulfuric acid solution is 60%;
[0129] (2) Amination
[0130] 6.0 g of activated carbon fiber was put into 320 mL of toluene solution, and after stirring evenly, 0.8 g of fatty acid polyethylene glycol ester and 1.1 g of polyvinyl pyrrolidone were added, and the temperature was raised to 60 ° C at a rate of 1.2 ° C / min, and stirred at 330 rpm for 30 min. After the stirring was completed, 0.66 g of N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane was added, and the temperature was raised to 94 ° C at a rate of 1.0 ° C / min, and the reaction was stirred at 230 rpm for 13 h. After the reaction was completed, it was filtered, washed and dried to obtain modified carbon fiber;
[0131] The mass concentration of the toluene solution is 68%.
[0132] 3. Preparation of carbon fiber preform
[0133] The modified carbon fiber is combed and air-laid to obtain a carbon fiber web. The weight of the carbon fiber web is 64 g / m 2 ; Prepare 12K carbon fiber filaments with a carbon content of 98.0% into continuous fiber carbon cloth, and control the gram weight of the continuous fiber carbon cloth to 385g / m 2 ; The carbon fiber preform is prepared by alternately stacking the carbon fiber web and the continuous fiber carbon cloth using needle punching technology;
[0134] The angle of alternating stacking is controlled to be 0°, and the alternating stacking ratio of carbon fiber mesh and continuous fiber carbon cloth is 1:1, that is, a layer of carbon fiber mesh and a layer of continuous fiber carbon cloth are alternately stacked; the needle punching density is 35 needles / cm 2 The needle penetration depth is 12 cm and the density of the carbon fiber preform is 0.66 g / cm 3 .
[0135] 4. Compound
[0136] A carbon fiber preform and 4.5 times the mass of the functional slurry were added to the impregnation container for impregnation treatment. The impregnation time was 57 minutes and the impregnation pressure was 2.0 MPa. After the impregnation was completed, the preform was taken out and then placed at 125°C for heat preservation and curing for 3.2 hours, the temperature was increased to 152°C at a rate of 2.2°C / min, the temperature was kept at 152°C for curing for 4.3 hours, the temperature was increased to 155°C at a rate of 1.2°C / min, the temperature was kept at 185°C for curing for 5.3 hours, the temperature was increased to 204°C at a rate of 0.8°C / min, and the temperature was kept at 204°C for curing for 6.2 hours. After the heat preservation and curing was completed, an impregnated body was obtained.
[0137] 5. Post-processing
[0138] The impregnated body is placed in a carbonization furnace and carbonized under an argon atmosphere. The heating rate is 5.3℃ / min, the carbonization temperature is 1520℃, and the carbonization time is 1.6h. After the carbonization is completed, a carbonized body is obtained. Then the carbonized body is placed in an impregnation container and put into 4.5 times the mass of the functional slurry for impregnation again. The impregnation time is 114min, the impregnation pressure is 2.4MPa, and the impregnation temperature is 183℃. After the impregnation is completed, it is placed in a carbonization furnace and carbonized under an argon atmosphere. The heating rate is 5.3℃ / min, the carbonization temperature is 1820℃, and the carbonization time is 1.4h. After the carbonization is completed, a carbon-carbon composite material is obtained.
[0139] Comparative Example 1
[0140] Based on Example 1, the changes are as follows:
[0141] In the step of preparing the functional slurry, the modification and functionalization steps are omitted;
[0142] In the slurry mixing step, the functional graphite is replaced by pretreated graphite in equal amounts;
[0143] The rest of the operations are the same.
[0144] Comparative Example 2
[0145] Based on Example 1, the changes are as follows:
[0146] (1) In the slurry mixing step, the ferric chloride component is replaced with coal tar pitch powder in equal amounts;
[0147] (2) In the step of modifying the carbon fiber, the plasma treatment in the activation step is omitted, that is, the carbon fiber is directly immersed in an acid solution for 2.5 hours at a temperature of 83°C. After the immersion, the carbon fiber is washed and dried to obtain an activated carbon fiber;
[0148] In the amination step, fatty acid polyethylene glycol ester and polyvinyl pyrrolidone are replaced with toluene solution in equal amounts;
[0149] The rest of the operations are the same.
[0150] Performance Testing
[0151] The products obtained in Examples 1-3 and Comparative Examples 1-2 were subjected to performance tests, as follows:
[0152] 1. Basic performance
[0153]
[0154] 2. Stable performance
[0155] The products obtained in Example 1-3 and Comparative Example 1-2 were first heated to 800°C at a rate of 10°C / min, placed at 800°C for 48 hours, cooled naturally to room temperature, and then placed at a strength of 500W / cm 2 The samples were irradiated under ultraviolet light for 72 hours, then heated to 1400°C at a rate of 5°C / min, left at 1400°C for 24 hours, cooled naturally to room temperature, and the mechanical properties were tested again. The details are as follows:
[0156]
[0157] The present invention performs functional treatment on graphite. First, the graphite is modified, which can enhance the dispersion performance of the graphite and increase the reactive groups on the surface of the graphite. Then, after functional treatment, the surface active groups of the modified graphite undergo a ring-opening reaction with epoxy soybean oil under the catalytic action of tin tetrachloride to form a stable network structure. The introduced epoxy soybean oil contains a hydrophobic alkyl long chain, which further enhances the compatibility with asphalt. In the slurry preparation step, the coal tar powder is mixed with an iron ion source and combined with an auxiliary agent component to improve the homogeneity and bonding performance of the slurry. The present invention modifies carbon fiber. First, the carbon fiber is subjected to oxygen plasma treatment and acid leaching to increase the surface roughness of the carbon fiber, thereby activating the carbon fiber. Then, the carbon fiber is subjected to an amination treatment to graft amino groups on the surface of the carbon fiber, which can react with epoxy groups in the functional slurry, thereby improving the binding force between the carbon fiber preform and the functional slurry, forming a stable structure and a good bonding interface, and enhancing the mechanical properties and stability of the carbon-carbon composite material.
[0158] The present invention adopts a specific method to prepare functional slurry and modified carbon fiber. The functional slurry has good homogeneity, and the components are tightly and stably bonded. In the impregnation step, the bonding interface between the carbon fiber preform and the functional slurry is good, and the impregnation is sufficient and uniform, so that the carbon fiber preform and the functional slurry are fully and firmly bonded, the structure is stable, and the compressive strength of the carbon-carbon composite material is guaranteed. The mechanical properties are excellent and stable, and the mechanical properties are still good under high temperature and ultraviolet radiation.
[0159] Comparative Example 1 omits the modification and functionalization steps of graphite. Graphite is easy to agglomerate and has poor compatibility with asphalt, which in turn affects the homogeneity of the slurry. In addition, in the compounding step, the interface bonding between the slurry and the carbon fiber preform is poor, and the impregnation is poor, which greatly affects the mechanical properties and stability of the product and seriously shortens the service life.
[0160] In Comparative Example 2, in the step of modifying the carbon fiber, the plasma operation in the activation step was omitted, which resulted in insufficient activation of the carbon fiber and affected the surface activation performance. In the amination step, fatty acid polyethylene glycol ester and polyvinyl pyrrolidone were replaced with toluene solution in equal amounts, resulting in uneven amination of the carbon fiber. In the step of compounding with the functional slurry not containing an iron ion source, the interfacial bonding force between the carbon fiber preform and the slurry was weak, and the final product had an uneven structure and unstable performance, which affected the comprehensive performance of the product.
[0161] Unless otherwise specified, all ratios and percentages described in the present invention are by mass ratios and percentages are by mass percentages.
[0162] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for improving the mechanical properties of carbon-carbon composite materials by iron ion doping modification, characterized in that: The method comprises the steps of preparing functional slurry, modifying carbon fiber, preparing carbon fiber preform, compounding and post-processing; The preparation of the functional slurry comprises the steps of pretreatment, modification, functionalization and slurry mixing; The modification step comprises placing the pretreated graphite in a closed container, spraying the modifier at a spraying rate of 2.8-3.2 g / min, stirring while spraying at a stirring rate of 265-275 rpm, increasing the pressure to 1.6-1.8 MPa, controlling the temperature to 60-64° C., increasing the speed to 343-356 rpm, and continuing stirring for 2.4-2.6 h. After the stirring is completed, filtering, washing, and drying to obtain the modified graphite; The modifier is composed of anhydrous ethanol, diisopropanolamine, castor oil and Tween 80; The functionalization step comprises adding modified graphite and dimethyl sulfoxide to a reaction container, stirring evenly, heating to 65-70°C at a rate of 1.4-1.6°C / min and stirring, stirring evenly, cooling to 40-45°C at a rate of 0.8-1.2°C / min, adding epoxidized soybean oil and tin tetrachloride, and performing ultrasonic treatment. After the ultrasonic treatment, stirring and reacting for 6.2-6.5h, filtering, washing, and drying after the reaction is completed to obtain functional graphite; The slurry mixing step comprises mixing coal tar powder and an iron ion source, performing ultrasonic oscillation treatment, and after the treatment, putting the mixture into a polytetrafluoroethylene ball ink tank, adding functional graphite for a first ball milling treatment, using zirconium oxide balls with a diameter of 5 mm as grinding balls, and adding anhydrous ethanol as a solvent medium. After the first ball milling treatment, methyl cellulose solution, polyethylene glycol 400 and Triton X-100 are added to continue a second ball milling treatment. After the ball milling treatment, a functional slurry is obtained; The modified carbon fiber comprises activation and amination steps; The activation step comprises placing the carbon fiber in a radio frequency low-pressure plasma device for plasma treatment, wherein the treatment atmosphere is oxygen, the treatment pressure is 6.7-7.2 Pa, the treatment power is 74-80 W, the oxygen flow rate is controlled to be 38-43 sccm, the treatment time is 4.5-5.5 min, and after the treatment, the carbon fiber is placed in an acid solution for immersion, and after the immersion, the carbon fiber is washed and dried to obtain an activated carbon fiber; The amination step comprises the following steps: putting the activated carbon fiber into a toluene solution, stirring evenly, adding fatty acid polyethylene glycol ester and polyvinyl pyrrolidone, heating to 56-60°C at a rate of 0.8-1.2°C / min, stirring at 310-330rpm for 23-30min, adding N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane after the stirring is completed, heating to 90-94°C at a rate of 0.6-1.0°C / min, stirring at 210-230rpm for reaction for 11-13h, and filtering, washing and drying after the reaction is completed to obtain the modified carbon fiber.
2. The method for improving the mechanical properties of carbon-carbon composite materials by iron ion doping modification according to claim 1, characterized in that: The pretreatment step comprises placing the graphite in deionized water for ball milling, using zirconia balls with a diameter of 5 mm as grinding balls, a ball-to-material ratio of 3-5:1, and a ball milling time of 37-43 minutes. After the ball milling is completed, drying is performed at 112-118° C. to obtain pretreated graphite; The particle size of the graphite is 210-230nm; The mass ratio of the graphite to the deionized water is 9.5-10.4:60-67.
3. The method for improving the mechanical properties of carbon-carbon composite materials by iron ion doping modification according to claim 1, characterized in that: In the modification step, the mass ratio of the pretreated graphite to the modifier is 8.7-9.1:55-60; The mass ratio of the anhydrous ethanol, diisopropanolamine, castor oil and Tween 80 is 76-80:1.3-1.5:1.0-1.2:1.8-2.
2.
4. The method for improving the mechanical properties of carbon-carbon composite materials by iron ion doping modification according to claim 1, characterized in that: In the functionalization step, the mass volume ratio of the modified graphite, dimethyl sulfoxide, epoxy soybean oil and tin tetrachloride is 10.2-10.6 g: 270-290 mL: 0.40-0.45 g: 0.01-0.02 g; The ultrasonic treatment has an ultrasonic time of 20-24 min, an ultrasonic power of 120-130 W, and an ultrasonic frequency of 23-30 kHz.
5. The method for improving the mechanical properties of carbon-carbon composite materials by iron ion doping modification according to claim 1, characterized in that: In the slurry mixing step, the iron ion source is one of ferric chloride and ferric oxide; The particle size of the coal tar powder is 95-110 mesh; The mass fraction of the methyl cellulose solution is 3.6-4.0%; The mass volume ratio of the coal tar powder, the iron ion source, the functional graphite, the anhydrous ethanol, the methyl cellulose solution, the polyethylene glycol 400, and the Triton X-100 is 96-99 g: 1.0-4.0 g: 13.4-14.0 g: 38-42 g: 58-62 g: 0.8-1.2 mL: 0.9-1.1 mL; The ultrasonic oscillation treatment has a treatment time of 24-30 minutes and a treatment frequency of 42-47kHz; The first ball milling treatment has a ball milling time of 7.8-8.2 hours, a ball milling speed of 172-185 rpm, and a ball-to-material ratio of 3-5:1; The secondary ball milling treatment has a ball milling time of 1.7-2.3 h, a ball milling speed of 232-247 rpm, and a ball-to-material ratio of 4-6:
1.
6. The method for improving the mechanical properties of carbon-carbon composite materials by iron ion doping modification according to claim 1, characterized in that: In the activation step, the carbon fiber has a length of 4.5-5.5 cm and a carbon content of 97.0-98.0%; The mass ratio of the carbon fiber to the acid solution is 6.3-6.7:38-42; The acid solution is a mixture of a nitric acid solution and a sulfuric acid solution, the volume ratio of the nitric acid solution to the sulfuric acid solution is 0.7-1.2:1, the mass concentration of the nitric acid solution is 60-64%, and the mass concentration of the sulfuric acid solution is 56-60%; The soaking time is 2.3-2.7 hours and the soaking temperature is 81-85°C.
7. The method for improving the mechanical properties of carbon-carbon composite materials by iron ion doping modification according to claim 1, characterized in that: In the amination step, the mass concentration of the toluene solution is 63-68%; The mass volume ratio of the activated carbon fiber, toluene solution, fatty acid polyethylene glycol ester, polyvinyl pyrrolidone, and N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane is 5.6-6.0 g: 280-320 mL: 0.6-0.8 g: 0.9-1.1 g: 0.62-0.66 g.
8. The method for improving the mechanical properties of carbon-carbon composite materials by iron ion doping modification according to claim 1, characterized in that: The step of preparing the carbon fiber preform is to comb the modified carbon fiber and obtain a carbon fiber web by air-laying technology. The carbon fiber web has a gram weight of 60-64 g / m 2 ; Prepare 12K carbon fiber filaments with a carbon content of 97.0-98.0% into continuous fiber carbon cloth, and control the gram weight of the continuous fiber carbon cloth to 370-385g / m 2 ; The carbon fiber preform is prepared by alternately stacking the carbon fiber web and the continuous fiber carbon cloth using needle punching technology; The angle of alternating stacking is controlled to be 0°, and the alternating stacking ratio of carbon fiber mesh and continuous fiber carbon cloth is 1:1, that is, a layer of carbon fiber mesh and a layer of continuous fiber carbon cloth are alternately stacked; the needle punching density is 32-35 needles / cm 2 The needle penetration depth is 9-12 cm, and the density of the carbon fiber preform is 0.62-0.66 g / cm 3 .
9. The method for improving the mechanical properties of carbon-carbon composite materials by iron ion doping modification according to claim 1, characterized in that: The compounding step comprises: adding a carbon fiber preform and 3.5-4.5 times the mass of a functional slurry into an impregnation container for impregnation treatment, wherein the impregnation time is 52-57 minutes and the impregnation pressure is 1.6-2.0 MPa. After the impregnation is completed, the preform is taken out and then placed at 115-125° C. for heat preservation and curing for 2.8-3.2 hours, the temperature is increased to 148-152° C. at a rate of 1.8-2.2° C. / min, and the preform is heat-insulated and cured at 148-152° C. for 3.7-4.3 hours, the temperature is increased to 175-185° C. at a rate of 0.8-1.2° C. / min, and the preform is heat-insulated and cured at 175-185° C. for 4.7-5.3 hours, the temperature is increased to 197-204° C. at a rate of 0.5-0.8° C. / min, and the preform is heat-insulated and cured at 197-204° C. for 5.8-6.2 hours. After the heat preservation and curing is completed, an impregnated body is obtained.
10. The method for improving the mechanical properties of carbon-carbon composite materials by iron ion doping modification according to claim 1, characterized in that: The post-treatment step is to place the impregnated body in a carbonization furnace, carbonize it in an argon atmosphere, the heating rate is 4.7-5.3°C / min, the carbonization temperature is 1480-1520°C, and the carbonization time is 1.4-1.6h. After the carbonization is completed, a carbonized body is obtained, and then the carbonized body is placed in an impregnation container, and is put into 3.5-4.5 times the mass of the functional slurry for impregnation treatment again, the impregnation time is 105-114min, the impregnation pressure is 2.0-2.4MPa, and the impregnation temperature is 175-183°C. After the impregnation is completed, it is placed in a carbonization furnace and carbonized in an argon atmosphere, the heating rate is 4.7-5.3°C / min, the carbonization temperature is 1760-1820°C, and the carbonization time is 1.4-1.8h. After the carbonization is completed, a carbon-carbon composite material is obtained.
